The Influence Fear of Missing Out against Social Media Addiction in Early Teens - Ester Ana (International Islamic Schools Alliance, 2021)
This study aims to determine how much influence is between fear of missing out (FoMO) and addiction to social media in early teens.. This study involved one dependent variable, namely social media addiction and one independent variable that influenced it, namely: fear of missing out (FoMO). There were 152 subjects in this study. The subjects of this study were adolescents aged 12-15 years who have social media such as Instagram, Facebook and Twitter. The research method used the Likert scale and data analysis using the product moment correlation, the result was r = 0.593. The higher the fear of missing out, the higher the addiction to social media, and vice versa. The contribution between fear of missing out (FoMO) and addiction to social media in early adolescents was 0.351 or 35.1% explained by the fear of missing out (FoMO) variable, while the remaining 64.9% was explained by other variables